Strategic Deployment of ICU Nurses in Response to the Omicron Variant Epidemic in Shanghai - Gao L; Tang S; Zheng W (Dove Medical Press, 2023)
Leiqing Gao,1,2,* Shi Tang,1,* Weiyan Zheng1 1Department of Nursing, Ren Ji Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People's Republic of China; 2Department of Nursing, Pu Jiang Hospital, Minhang District, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Weiyan Zheng, Ren Ji Hospital, Shanghai Jiao Tong University School of Medicine, 160 Pujian Road, Pudong District, Shanghai, 200127, People's Republic of China, Fax +86-21-63730455, Email renji_zhengweiyan@163.comObjective: In the first half of 2022, Shanghai faced the challenge of an emerging wave of epidemics caused by the Omicron variant. In response, 48 hospitals, spanning municipal and district levels, were rapidly converted into designated hospitals. This case study focuses on the South Branch of Renji Hospital, School of Medicine, Shanghai Jiaotong University, as one such designated hospital.Methods: Facing unprecedented challenges without prior experience, we devised a strategic approach to deploy ICU nurses effectively. This approach involved crisis event gradation, establishing a human resources pool, and classifying nursing staff based on qualifications and proficiencies.Results: By May 11, 2022, all 48 designated hospitals were operational. The South Branch of Renji Hospital treated 3310 Omicron-infected patients between April 7 and June 21, 2022, including 115 critically ill patients in a 38-bed ICU. We meticulously assigned 136 nurses, distributed as follows: Grade A 12.5%, Grade B 12.5%, Grade C 40%, and Grade D 35%, with three specialized nursing managers. Nurses worked tirelessly in 4-hour shifts, wearing full protective gear. Remarkably, the hospital maintained a flawless record, with no nursing-related adverse events and zero patient mortality in the ICU.Conclusion: Effective management of ICU nursing personnel is associated with patient safety. Strategic rostering and placement of ICU nurses in designated hospitals optimize resource utilization, enhancing service effectiveness and working conditions. This technique is a crucial resource for hospitals facing unforeseen public health crises requiring rapid ICU nurse resource allocation and management.Keywords: Omicron variant, pandemic response, designated hospital, ICU, nurse, human resource management, resource allocation